PO 8515 Capacity building in preparation for an HIV vaccine trial: the globally relevant AIDS vaccine europe-africa trials partnership (GREAT). (24th April 2019) - Kilembe, William; Okech, Brenda; Nielsen, Leslie; Muturi-Kioi, Vincent; Jaoko, Walter; Mutua, Gaudensia; Sanders, Eduard; Mpendo, Juliet; Gumbe, Anne; Chinyenzi, Kundai; Bont, Jan De; Kuipers, Hester; et al.
Abstract : Background: The Globally Relevant AIDS Vaccine Europe-Africa Trials (GREAT) partnership is an EDCTP-funded project that aims to foster collaboration between institutions in Europe and sub-Saharan Africa to build capacity among African clinical research centres (CRCs) for the design and conduct of HIV-1 vaccine efficacy trials. Methods: In January 2017, the University of Oxford (UOXF) and five CRCs in Kenya, Uganda and Zambia were awarded a 5 year grant for capacity building and to support conduct of an HIV-1 vaccine trial in different high-risk populations across Africa using cross-clade (conserved protein regions) T-cell vaccines. UOXF and CRCs embarked on activities to strengthen capacity of the CRCs for future efficacy trials. This included training, community engagement, cohort preparation and infrastructure upgrade. Results: In the first year, the African investigators at the CRCs collaborated on the development of a protocol aimed at assessing the safety and immunogenicity of the tHIVconsvX vaccines. In preparation for the planned vaccine trial, infrastructure upgrades were prioritised at all partner sites and this included building laboratory space and procurement of appropriate laboratory equipment. Planned infrastructure upgrades will also ensure that high-risk populations can be safely and confidentially included in HIV prevention clinical trials. Systematic community engagement was implemented at all sites, training in GCP/GCLP was provided and training is planned for nominated CRC staff to lead community engagement efforts. Conclusion: Improved infrastructure and the provision of targeted training will enhance future trials and increase the capacities of CRCs and staff to conduct quality trials in previously hard-to-reach populations. Early collaboration between investigators from European and sub-Saharan African institutions, with equal responsibilities in the protocol development process, established a meaningful partnership. EDCTP funding also offers a unique opportunity for capacity building.